Answer:
6 CaC₂(s) + 16 H₂O(g) + 3 CO₂(g) → 6 Ca(OH)₂(s) + 5 CH₂CHCO₂H(g)
Step-by-step explanation:
There are two steps in the preparation of acrylic acid.
Step 1: CaC₂(s) + 2 H₂O(g) → C₂H₂(g) + Ca(OH)₂(s)
Step 2: 6 C₂H₂(g) + 3 CO₂(g) + 4 H₂O(g) → 5 CH₂CHCO₂H(g)
In the net chemical equation, intermediaries do not appear, C₂H₂ in this case. To achieve this, we will multiply the first step by 6, add it to the second step and cancel what is on both sides of the equation.
6 CaC₂(s) + 12 H₂O(g) → 6 C₂H₂(g) + 6Ca(OH)₂(s)
+
6 C₂H₂(g) + 3 CO₂(g) + 4 H₂O(g) → 5 CH₂CHCO₂H(g)
-----------------------------------------------------------------------------------------------------
6 CaC₂(s) + 12 H₂O(g) + 6 C₂H₂(g) + 3 CO₂(g) + 4 H₂O(g) → 6 C₂H₂(g) + 6Ca(OH)₂(s) + 5 CH₂CHCO₂H(g)
6 CaC₂(s) + 16 H₂O(g) + 3 CO₂(g) → 6 Ca(OH)₂(s) + 5 CH₂CHCO₂H(g)